Nutrition and food science & technology: Vital symbiosis for sustainable health - Gert W. Meijer (Future Foods)
Nutrition science and food science & technology are crucial for creating a healthier world through accessible nutrition and sustainable health practices. Examples of successful impact can be found in food fortification, foods with effective levels of bioactives, (re)formulation of foods to combat obesity and diet-related diseases, (re)formulation of foods to enable nutrition and health claims, and the activities by the European Technology Platform (ETP) for the food sector 'Food for Life'.In preparing, maintaining, and promoting the Strategic Research and Innovation Agenda (SRIA), the ETP aims to identify scientific and technological actions towards the transformations that are needed to achieve more optimal outcomes of the food system. The four major food system outcomes are the environment, society, citizen health & wellbeing, and economy & competitiveness. The SRIA provides essential guidance to the European Commission, Member States and Regions, the food industry, and the wider research community interested in food, in the form of Research and Innovation needs to make a real difference to the Food and Drink sector and society. The mutualism between nutritionists and food scientists and technologists is essential for achieving the transformations towards the outcomes that are needed for a more sustainable food system.